Роль неколагенових білків у in vitro мінералізації: дослідження зв'язування кальцію з остеокальцином методом наноспрей мас-спектрометрії - Суходуб, Л.Ф.; Гелінскі, М.; Калінкевич, О.М.; Рюль, Р.; Шпрінгер, А.; Ліншайд, М.; Помпе, В. (Видавничий дім "Академперіодика" НАН України, 2008)
The NSI-MS technology is used to study the calcium-osteocalcin (OC) and calcium phosphate-OC interactions and the influence of the most abundant noncollagenous protein of bone on the in-vitro mineralization. NSI-FTICR mass spectra show peaks of osteocalcin in pure and oxygenated forms. Both forms are shown to bind three Ca^²+ ions per one OC molecule. Binding with pure OC is characterized by much stronger interactions due to the possible ionic bridging with Gla residues of the OC molecule. The previous NSI-FTICR studies of the more complicated OC+ Ca/P system demonstrate the presence of small stable calcium-phosphate clusters bound with OC.